2015
DOI: 10.1371/journal.pgen.1005207
|View full text |Cite|
|
Sign up to set email alerts
|

A Simple Auxin Transcriptional Response System Regulates Multiple Morphogenetic Processes in the Liverwort Marchantia polymorpha

Abstract: In land plants comparative genomics has revealed that members of basal lineages share a common set of transcription factors with the derived flowering plants, despite sharing few homologous structures. The plant hormone auxin has been implicated in many facets of development in both basal and derived lineages of land plants. We functionally characterized the auxin transcriptional response machinery in the liverwort Marchantia polymorpha, a member of the basal lineage of extant land plants. All components known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
205
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 178 publications
(217 citation statements)
references
References 83 publications
7
205
1
4
Order By: Relevance
“…Furthermore, protocols for efficient Agrobacterium -mediated transformation of spores have been pioneered (Ishizaki et al, 2008), and these may be able to be adapted, with modifications to suit differences in life cycle, to other spore-producing land plants. Studies on the auxin transcriptional response machinery in M. polymorpha have suggested that auxin response modulates, but does not determine cell fates and, furthermore, that it is critical for the transition from 2-dimensional growth to 3-dimensional growth in the haploid generation (Kato et al, 2015; Flores-Sandoval et al, 2015). Gene knockout technologies also enabled the discovery that the molecular mechanism by which plants measure photo-period and control the transition between vegetative growth and reproductive growth is broadly conserved across land plants (Kubota et al, 2014).…”
Section: Land Plant Evolutionmentioning
confidence: 99%
“…Furthermore, protocols for efficient Agrobacterium -mediated transformation of spores have been pioneered (Ishizaki et al, 2008), and these may be able to be adapted, with modifications to suit differences in life cycle, to other spore-producing land plants. Studies on the auxin transcriptional response machinery in M. polymorpha have suggested that auxin response modulates, but does not determine cell fates and, furthermore, that it is critical for the transition from 2-dimensional growth to 3-dimensional growth in the haploid generation (Kato et al, 2015; Flores-Sandoval et al, 2015). Gene knockout technologies also enabled the discovery that the molecular mechanism by which plants measure photo-period and control the transition between vegetative growth and reproductive growth is broadly conserved across land plants (Kubota et al, 2014).…”
Section: Land Plant Evolutionmentioning
confidence: 99%
“…Gene expression associated with ARF activation has been implicated in diverse processes in land plants, including tropic responses and the establishment of polarity, as well as embryogenesis and organogenesis in flowering plants, and both gametophyte and sporophyte development in nonflowering plants (De Smet and Jurgens, 2007;Banks, 2009;Moller and Weijers, 2009;Prigge et al, 2010;Vernoux et al, 2010;Bennett et al, 2014;Flores-Sandoval et al, 2015;Kato et al, 2015). At the cellular level, auxin affects all aspects of cellular growth, including cell elongation, cell division and differentiation (Perrot-Rechenmann, 2010;Takatsuka and Umeda, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…www.plantphysiol.org/cgi/doi/10.1104/pp.17.00274 (Kato et al, 2015), but the M. polymorpha and P. patens genomes contain homologs of the canonical auxin-signaling factors TIR1/AFB, Aux/IAA, and AUXIN RESPONSE FACTOR (ARF; Kato et al, 2015). These auxin-signaling components regulate normal cell elongation and differentiation in M. polymorpha (Flores-Sandoval et al, 2015;Kato et al, 2015). Consequently, auxin-related genes show very few differences between land-plant lineages (Finet and Jaillais, 2012), suggesting that the last common ancestor of land plants had already acquired the core auxin machinery of land plants.…”
mentioning
confidence: 99%